A critical analysis of the role and nature of dynamic capabilities to enable and sustain organizational fitness, incorporating complexity thinking - Schick, Verena (Stellenbosch : Stellenbosch University, 2012)
Thesis (MComm)--Stellenbosch University, 2002.